The role of the Pseudomonas aeruginosa hypermutator phenotype on the shift from acute to chronic virulence during respiratory infection - Hall, Kalen M.; Pursell, Zachary F.; Morici, Lisa A. (Frontiers in Cellular and Infection Microbiology, 2022)
Chronic respiratory infection (CRI) with Pseudomonas aeruginosa (Pa) presents many unique challenges that complicate treatment. One notable challenge is the hypermutator phenotype which is present in up to 60% of sampled CRI patient isolates. Hypermutation can be caused by deactivating mutations in DNA mismatch repair (MMR) genes including mutS, mutL, and uvrD. In vitro and in vivo studies have demonstrated hypermutator strains to be less virulent than wild-type Pa. However, patients colonized with hypermutators display poorer lung function and a higher incidence of treatment failure. Hypermutation and MMR-deficiency create increased genetic diversity and population heterogeneity due to elevated mutation rates. MMR-deficient strains demonstrate higher rates of mucoidy, a hallmark virulence determinant of Pa during CRI in cystic fibrosis patients. The mucoid phenotype results from simple sequence repeat mutations in the mucA gene made in the absence of functional MMR. Mutations in Pa are further increased in the absence of MMR, leading to microcolony biofilm formation, further lineage diversification, and population heterogeneity which enhance bacterial persistence and host immune evasion. Hypermutation facilitates the adaptation to the lung microenvironment, enabling survival among nutritional complexity and microaerobic or anaerobic conditions. Mutations in key acute-to-chronic virulence “switch” genes, such as retS, bfmS, and ampR, are also catalyzed by hypermutation. Consequently, strong positive selection for many loss-of-function pathoadaptive mutations is seen in hypermutators and enriched in genes such as lasR. This results in the characteristic loss of Pa acute infection virulence factors, including quorum sensing, flagellar motility, and type III secretion. Further study of the role of hypermutation on Pa chronic infection is needed to better inform treatment regimens against CRI with hypermutator strains.